The association between uncertainty intolerance, perceived environmental uncertainty, and ego depletion in early adulthood: the mediating role of negative coping styles - Li, Xiao; Song, Jingjing (Frontiers in Psychology, 2024)
Uncertainty intolerance and perceived environmental uncertainty can influence an individual's emotions and behavioral responses. Previous research showed that high uncertainty intolerance and high perceived environmental uncertainty were both negatively associated with an individual's life satisfaction. We explored the association between uncertainty intolerance, perceived environmental uncertainty, and ego depletion in early adulthood. Investigating 292 college students using an uncertainty intolerance scale, a perceived environmental uncertainty scale, a negative coping styles questionnaire, and an ego depletion scale. The correlations among all variables were calculated using Pearson's product-moment correlation coefficient, and then we used the PROCESS macro (model 8) in SPSS to test the conditional process model in the relationship between uncertainty intolerance and ego depletion. The results showed that the interaction terms of uncertainty intolerance and perceived environmental uncertainty were significantly associated with negative coping styles. Only in the high perceived environmental uncertainty situations, uncertainty intolerance was positively associated with negative coping styles, and negative coping styles were positively associated with ego depletion. In general, compared with perceived environmental uncertainty, participants' cognition towards environmental uncertainty was much more associated with individual's coping styles and psychological state, individuals with high uncertainty intolerance would face great stress and experience more emotional problems. Our results suggest that it is important for individuals' mental health to gain a sense of control in an uncertain environment and improve their tolerance of uncertainty. Future research needs to pay attention to the intervention strategy of decreasing uncertainty intolerance.